Lifestyles and Surveillance of Sexual and Reproductive Women's Health. (5th February 2016) - Ferreira, M.; Ferreira, S.; Ferreira, N.; Andrade, J.; Chaves, C.; Duarte, J.
Abstract: Background: The epidemic increase of diseases is closely related to lifestyle changes. The low adhesion to breast self-examination and cervical cytology hinders prevention and early diagnosis during the asymptomatic state of two silent diseases, with nonspecific symptoms that are a major cause of death by cancer in the Portuguese female population. Objectives: To analyze the influence of sociodemographic variables and lifestyles in the surveillance of sexual and reproductive health of Portuguese women. Methods: Quantitative, non-experimental, correlational and cross-sectional study, conducted with a non-probabilistic convenience sample of 522 women aged between 18 and 67 years old, who applied the questionnaires about Breast self-examination, Knowledge about cervical cancer and the Inventory "My Lifestyle" (Ribeiro, 1993. Results: The average age of women is 38.89 years old. Women aged 31-37 years old (28.6%), Portuguese (99.1%), cohabiting with a partner and / or child (74.0%), with an active employment status (67 5%), residing in urban areas (55.8%) with higher education and attending family planning consultations have better lifestyles, without statistical significance (F = 0.016, p = 0.899). Conclusions: Healthy behaviors and lifestyles are crucial to good overall health. Adhesion to surveillance of sexual and reproductive women's health is influenced by several factors, including the place of residence, employment status and lifestyles. These variables must be considered by health professionals when planning periodic screenings.